The Structure and Dynamics of Modern United States Federal Case Law - Adusumilli, Keerthi; Brown, Bradford; Harrison, Joey; Koehler, Matthew; Kutarnia, Jason; Michel, Shaun; Olivier, Max; Pfeifer, Craig; Slater, Zoryanna; Thompson, William; Vetter, Dianna; Zacharowicz, Renee (Frontiers in Physics, 2022)
The structure and dynamics of modern United States Federal Case Law are examined here. The analyses utilize large-scale network analysis tools, natural language processing techniques, and information theory to examine all the federal opinions in the Court Listener database, containing approximately 1.3 million judicial opinions and 11.4 million citations. The analyses are focused on modern United States Federal Case Law, as cases in the Court Listener database range from approximately 1926 to 2020 and include most Federal jurisdictions. We examine the data set from a structural perspective using the citation network, overall and by time and space (jurisdiction). In addition to citation structure, we examine the dataset from a topical and information theoretic perspective, again, overall and by time and space.